Real-time prediction models for remaining cold start time in proton exchange membrane fuel cell based on stack temperature - Huiying Zhang; Yuhang Wang; Suoying He; Ming Gao (Case Studies in Thermal Engineering, 2023)
In order to mitigate the irreversible damage caused by cold start and preserve cell performance, this paper proposes a real-time prediction method based on the remaining cold start time of the proton exchange membrane fuel cell (PEMFC). This method can protect the cell by referencing the current cold start effect. In this work, a real-time prediction model for the remaining cold start time based on the backpropagation (BP) neural network, long short-term memory (LSTM) neural network, and nonlinear regression of logarithmic function is established. Furthermore, a combined prediction model with variable weight is established by integrating these three prediction methods. Results demonstrated that, when considering two distinct cold start experimental conditions as samples, the average prediction accuracy of the three single models across all prediction times is 78.80%, 71.76%, 67.07% and 84.72%, 84.66%, 87.03%, respectively. In comparison to the optimal single prediction model, the combined prediction model exhibits an improvement in prediction accuracy by 9.84% and 2.83% under the two different experimental conditions, respectively. In addition, the maximum average prediction error between predicted values and actual values at each time instant within a range of only 3 s, thereby providing substantial support for accurate cold start performance prediction.